Vitamin D – new trend or real benefis? - Sobstyl, Małgorzata; Tkaczuk-Włach, Joanna; Sobstyl, Jacek; Jakiel, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2013)
Vitamin D supplementation plays an important role in the skeleton and calcium metabolism. The results of studies published in the 21 st century suggest that vitamin D supports the function of the heart, brain, muscle and plays an important role in cancer (e.g. breast, colorectal, prostate cancer). Serum concentration of 25-OHD is a biomarker of the vitamin D status. The optimal concentration of 25-OHD is between 30 and 80 ng/ml. The daily dose of vitamin D should be between 800 and 1000 IU. For adults, vitamin D supplementation is suggested from October to March.